Operation: secret recipe - Stilton, Geronimo (Geronimo Stilton, 2017)
In Milan to attend the unveiling of a parchment that contains the original recipe for a traditional holiday bread, Geronimo Stilton is shocked when a thief posing as him steals the recipe, forcing him to catch the culprit and clear his name.